THE ROLE OF CYTOKINE PROFILE IN THE DEVELOPMENT OF ACUTE RENAL PATHOLOGY IN CHILDREN WITH COVID -19 - Ismoilova, Z.A.; Xasanov, I.O.; Rayimberganova, G.Sh.; Madaminova, A.Q.; Yaqubova, Z.O. (PT. Antis International Publisher, 2025)
Objective: This study aimed to investigate the impact of Covid-19 on the development of tubulointerstitial kidney damage in children, focusing on cytokine profiles, kidney function, and the role of neutrophil gelatinase-associated lipocalin (NGAL) as a marker for kidney injury. Methods: A cohort of 132 children who experienced tubulointerstitial kidney damage post-Covid-19 was studied. The patients were divided into two groups: one with acute pyelonephritis (AP) and the other with acute tubulointerstitial nephritis (ATIN). Diagnostic methods included blood and urine analysis, renal ultrasound, cytokine profiling (IL-6, IL-4, TNF-α, γ-INF), and NGAL measurement. Results: The study found significantly elevated NGAL levels in the urine of children with AP and Covid-19 compared to healthy controls (110.74±1.27 vs. 65.66±0.64 ng/mg creatinine; p<0.001). Cytokine analysis revealed substantial increases in IL-6, TNF-α, and γ-INF, particularly in children with Covid-19-related kidney damage, suggesting a severe inflammatory response contributing to kidney dysfunction. Novelty: This research highlights the crucial role of cytokines in kidney injury following Covid-19 in children and emphasizes NGAL as a reliable biomarker for early detection of renal damage, offering new insights for treatment and prognosis.